Pembuatan Alat Pendeteksi Banjir di Sungai Kawasan Wisata Desa Rindu Hati Bengkulu Tengah - Junas Haidi; Hendy Santosa; Alex Surapati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Rindu Hati village is a village in Bengkulu province which developing natural tourism by utilizing the village budget managed by the village-owned enterprise. The tourism developed in Rindu Hati Village such as Glamping, Tubing, Waterfall Tracking, Endu Hill cliff climbing. The location of the village and tourist attractions are along the river and under the foot of the hill. In addition, the scene is very beautiful and it has the potential for a natural disaster if the rainy season occurs floods which can occur and the impact is cause loss of property and life. In the tourist attraction and residential areas, the residents of Rindu Hati Village have not been equipped with flood detectors. So, the negative impacts in the event of a flood are very large. To reduce the impact of floods, a flood detector was made as a warning sign to tourist visitors and residents when the flood or an increase in river water levels. The flood detector was made using a solar cell system and two controllers which will read the condition of the water level directly and could stand for 68 hours if there is no sunlight and could last for 8 hours when the siren sounds. The flood detection equipment has been installed and socialized in the term of theory and practice to tourism managers and the local community with the participant of 16 people. The flood detection was installed in the Rindu Hati Tourism River, it will reduce the impacts caused by floods and will increase the comfort of visitors from the dangers of flooding